Diffuse hypoplasia of the aortic arch and isthmus in a patient with Williams syndrome - İsmihan Selen Onan; Erkut Öztürk; Aylin Demirel Başgöze; Ayşe Çiçek; Burak Onan (KARE Publishing, 2017)
Williams syndrome is a rare neurodevelopmental disorder characterized by mental retardation, growth deﬁciency, hypercalcemia, cardiac defects, and a distinctive facial appearance. Cardiovascular abnormalities are present in approximately 80% of Williams syndrome patients. Surgical treatment is generally performed for supravalvular aortic stenosis, aortic coarctation, pulmonary artery stenosis, or ventricular septal defect. In rare cases, diffuse hypoplasia of the aortic arch with a normal left ventricular outflow tract and ascending aorta may be diagnosed in early childhood. Described herein is the case of a 16-month-old female with Williams syndrome and diffuse hypoplasia of the aortic arch and isthmus, and concomitant pulmonary stenosis and a ventricular septal defect. The patient underwent a successful surgical repair of the aortic arch with a modified pericardial patch technique.